Germination and regeneration mechanisms in Mediterranean degenerate forests - Bacilieri, R.; Bouchet, M. A.; Bran, D.; Grandjanny, M.; Maistre, M.; Perret, P.; Romane, F. (Journal of Vegetation Science, 1993)
Abstract. Germination and developmental behaviour during juvenile stages are of importance in relation to succession mechanisms acting on plant communities. This is particularly so in the Mediterranean region, where the climatic summer drought causes stress. We investigated and compared germination and development of four tree species in two parts of the French Mediterranean region where the original dominant tree species (Quercus pubescens) has been largely replaced by Quercus ilex in the southern part, and Castanea sativa in the northern part. Observed differences in germination rates and developmental behaviour, especially shootroot ratio and the role of water supply, suggest that other species may eventually replace the current dominant species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Castanea sativa; Pinus pinaster; Quercus ilex; Quercus pubescens

What are the consequences of being a downy oak (quercus pubescens) or a holm oak (Q. ilex) for breeding blue tits (Parus caeruleus)? - Blondel, J.; Isenmann, P.; Maistre, M.; Perret, P. (Plant Ecology, 1992)
By comparison with deciduous oaks, the lower yearly production of new leaves in sclerophyllous oaks is hypothesized to have several consequences on animal communities. In particular, the production of arthropod communities that feed upon the leaves should be lower in sclerophyllous than in deciduous oaks, this causing changes in breeding patterns and the demographic balance in insectivorous birds. Studies in both deciduous and sclerophyllous habitats in southern France have shown that: 1) the spring development of new leaves occurs later and more slowly in sclerophyllous than in deciduous oaks, 2) the biomass of caterpillars is much lower in sclerophyllous oak forests, and 3)there is a large variation in life history traits of the Blue Tit depending in which type of habitat they breed. Laying date occurs later and clutch size is lower in sclerophyllous habitats than in deciduous habitats. The evolution of life history traits is discussed according to whether poor sclerophyllous habitats are isolated (e.g. on Corsica) or are parts of landscapes including both habitat types.
Keywords: breeding traits; caterpillars; leafing phenology; Parus caeruleus; Quercus ilex; Quercus pubescens